Visualizing Narrative Structures: A Mixed-Methods Evaluation of Story Grammar Strategy in EFL Reading Classrooms - Gupuh Rahayu (ANTHOR: Education and Learning Journal, 2026)
The ability to read narrative texts often presents a cognitive challenge for English as a Foreign Language (EFL) learners due to the complexity of the text’s plot and structure. This study evaluates the effectiveness of the Story Grammar Strategy (SGS) as a tool for visualising macro-structure to improve students’ reading comprehension. Using a sequential explanatory mixed-methods design, this study involved 19 Year 8 students at a junior high school in Kupang. Quantitative data were collected through formative tests (pre-test and post-test), whilst qualitative data were obtained through classroom observations and semi-structured interviews. Quantitative analysis results showed a significant increase in the mean reading comprehension score, from 56.8 to 84.7, with 58% of students achieving the ‘excellent’ category. Qualitative analysis confirmed that the SGS worksheet served as a visual bridge facilitating students in systematically dissecting, organising, and reconstructing story elements. Furthermore, this strategy was found to enhance student engagement and affective motivation. This study concludes that visualising text structure through SGS is an effective instructional strategy for overcoming reading barriers in EFL classrooms.